Becotatug Vedotin Combined With Pucotenlimab in Platinum- and Immunotherapy-Resistant Recurrent or Metastatic Nasopharyngeal Carcinoma - Dan-Yun Ruan; Feng-Hua Wang; Yujuan Zhou; Yanqun Xiang; Jinguan Lin; Lin Liu; Ping Liu; Linquan Tang; Yuxiang Ma; Tao Hou; Qiuyan Chen; Zhi-Ming Li; et al. (Journal of Clinical Oncology, 2026)
PURPOSE Patients with recurrent or metastatic nasopharyngeal carcinoma (R/M NPC) have limited therapeutic options after failing platinum and anti–PD-1/PD-L1 therapy. We investigated the efficacy and safety of an epidermal growth factor receptor (EGFR)–directed antibody-drug conjugate (ADC) becotatug vedotin (BV) combined with a PD-1 inhibitor pucotenlimab in this setting of patients. MATERIALS AND METHODS Magic-C001 (ClinicalTrials.gov identifier: NCT05688605 ) is an ongoing, open-label, multicohort, dose escalation (phase I) and expansion (phase II) study in patients with EGFR-positive solid tumors. Eligible patients received pucotenlimab 3.0 mg/kg and BV at 1.8-2.3 mg/kg (phase I) or 2.0 mg/kg (phase II for NPC) once every 3 weeks. The primary end point for phase II was objective response rate (ORR). Secondary end points included duration of response (DoR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. RESULTS Among 31 patients with NPC at the recommended phase II dose (RP2D) from phase I and II who had received anti–PD-1/PD-L1 and platinum-based therapy, the confirmed ORR was 71.0% (95% CI, 52.0 to 85.8); DCR was 93.5% (95% CI, 78.6 to 99.2). The median DoR and PFS were 14.0 months (95% CI, 5.7 to not estimated) and 12.0 months (95% CI, 6.8 to 15.4), respectively. Median OS was not mature. Most common treatment-related adverse events (TRAEs) were pruritus (71.9%), hypoesthesia (65.6%), anemia (59.4%), and rash (56.3%). TRAEs of ≥grade 3 occurred in 40.6% of patients. No TRAEs led to death. CONCLUSION To our knowledge, we report the first trial combining an ADC with immunotherapy for platinum and anti–PD-1/PD-L1–resistant NPC. BV plus pucotenlimab yielded a notable ORR with exceptionally durable responses and substantially prolonged PFS, alongside manageable toxicities. This regimen may offer a promising anti–PD-1 rechallenge strategy in this population, which is being confirmed in an ongoing, multicenter, randomized controlled, phase III study.